Use of Topical Nitric-Zinc Complex Solution to Treat Palmoplantar and Periungual Warts in a Pediatric Population - Aniza Giacaman; Corinne Granger; Sonia Aladren; Ana Bauzá; Bárbara Alomar Torrens; María Riutort Mercant; Ana Martin-Santiago (Adis, Springer Healthcare, 2019)
Abstract Introduction Nitric-zinc complex solution (NZCS) is a topically applied solution containing nitric acid, zinc, copper, and organic acids that induce a painless caustic effect on "difficult-to-treat" warts, including palmoplantar and periungual locations. The objective of the present prospective clinical study was to describe the efficacy and tolerability of NZCS in the treatment of palmoplantar and periungual warts in children. Methods Eligible patients were immunocompetent children and adolescents, with at least one palmoplantar or periungual wart. NZCS was topically applied every 2 weeks in clinic. Efficacy was recorded by clinical evaluation, and acceptability assessments were measured using a visual analogue scale (VAS). Results Pediatric patients (N = 12) were equally distributed by gender, and the mean age was 9.60 ± 3.34 years. The youngest patient was 4 years old. A total of 31 warts were identified: 24 periungual warts (77.4%), 2 palmar warts (6.45%), and 5 plantar warts (16.12%). We observed complete resolution in 83.9% of the warts treated with NZCS, achieving total cure considered as therapy success in 87.5% of periungual warts and 71% of palmoplantar warts, with a mean of 6.0 treatment sessions. The esthetic results evaluated by the investigator were considered excellent in 83.3% of cases and good in 16.7%. In 100% of the completely resolved cases, no scars, erythema, hyperpigmentation, hypopigmentation, or hypertrophy in the area surrounding the treated warts were observed by the investigator. The esthetic results evaluated by the patients or parents/guardians were excellent. Pain and burning sensation were minimal and well tolerated. No clinically relevant adverse events were reported. Conclusion NZCS was an effective treatment of warts in this pediatric population. The painlessness, simplicity, and twice-monthly dosing regimen of this treatment represents an advantage over standard approaches. Funding ISDIN. Trial Registration Retrospectively registered 6 September 2019, ISRCTN90862249.